Effective time management for teaching effectiveness (2008)
This paper discusses the essence of time management arid its positive effect on teaming Inland subsequently on learning. Samples were selected in two phases of the study viz: a the outset when 31 schools were selected in Ibadan City and after phase one of the study when the most effective teacher-time-manager and the least-effective-teacher-time manager were v identified. Thirty students each from these classes were randomly selected and used a: the pretest -posttest experimental/control groups design to confirm or confound the resul s of jilone. Findings include: effective-time management resulted in effective and learning if Teachers were to be effective time managers they must minimize social activities and |devote more time preparation, good time management engenders improved student performance etc. Recommendations were that to assist teachers to manage their time better, they should be well remunerated; teachers should reduce their social activities to the b irest minimum; they should the business more seriously among others.